Factors influencing maternal health care in Nepal: The role of socioeconomic interaction - Sharmistha Self; Richard Grabowski (Asia-Pacific Sustainable Development Journal, 2019)
This paper relies on an extensive data set on Nepalese families to examine factors influencing the extent to which maternal health care is provided.